Comparison of Efficacy in the Treatment of Otomycosis using 10% Povidone-Iodine and Clotrimazole Solution: Randomized, Double-Blind Control Trial - Numchaichanakij, Pilasluck; Kreesaeng, Pattraporn (International Archives of Otorhinolaryngology, 2025)
The main treatment of otomycosis has required the use of topical antifungal drops and/or acidifying agents. However, because of the availability issues of antifungal drops in developing countries, treatment with acidifying agents alone is necessary.The objective of this study was to compare the efficacy in the treatment of otomycosis using a 10% povidone-iodine and clotrimazole solution.Patients with otomycosis were assigned to 10% povidone-iodine group and Clotrimazole group. The patients were evaluated on the response of each group at 1, 2,4 and 8 weeks.93 patients were assigned to the 10% povidone-iodine group and 95 patients to the Clotrimazole group. the response to treatment between groups. In the second week after treatment, 37.64% of the 10% povidone-iodine group and 40% of the Clotrimazole group had a good response to treatment (p = 0.551). In the fourth week after treatment, 52.69% of the 10% povidone-iodine group and 55.79% of the Clotrimazole group had a good response to treatment (p = 0.644). In the eighth week after treatment, 58.06% of the 10% povidone-iodine group and 64.21% of the Clotrimazole group had a good response to treatment (p = 0.642) In the 12th week after treatment, 76.34% of the 10% povidone-iodine group and 85.26% of the Clotrimazole group had a good response to treatment (p = 0.248).There were no significant differences in the response to between 10% povidone-iodine and Clotrimazole groups in the second, fourth, eighth and twelfths after treatment.
Keywords: otomycosis; otitis externa; fungus; antifungal; topical eardrop